Kako učencem, ki obiskujejo osnovnošolski program z nižjim izobrazbenim standardom, predstaviti pisatelja Franceta Bevka in jim približati njegova dela - Markič, Nataša (Šolska knjižnica, 2016)
The purpose of the paper is to present a lesson in library and information science with a composite class, which is attended by students with special needs and various deficiencies. The described example of practice is one of the lessons that is being implemented in agreement with the teacher and which is included in the school library's yearly plan for the class with an adapted programme and a lower educational standard. The writer France Bevk was presented to the students and we tried to get them to relate to his works; the preparation and implemetation of this lesson required more time, adjustments, simplifications and illustrations than usual. A greater amount of pictorial material was prepared and used: the set-up exhibition was helpful.
Keywords: branje; knjižnično informacijsko znanje; osnovne šole; Pastirci; slovenska književnost; šolske knjižnice; učenci s posebnimi potrebami; učne metode